Soluble Form of Canine Transferrin Receptor Inhibits Canine Parvovirus Infection In Vitro and In Vivo. (8th September 2013) - Wen, Jiexia; Pan, Sumin; Liang, Shuang; Zhong, Zhenyu; He, Ying; Lin, Hongyu; Li, Wenyan; Wang, Liyue; Li, Xiujin; Zhong, Fei
Abstract : Canine parvovirus (CPV) disease is an acute, highly infectious disease threatening the dog-raising industry. So far there are no effective therapeutic strategies to control this disease. Although the canine transferrin receptor (TfR) was identified as a receptor for CPV infection, whether extracellular domain of TfR (called soluble TfR (sTfR)) possesses anti-CPV activities remains elusive. Here, we used the recombinant sTfR prepared from HEK293T cells with codon-optimized gene structure to investigate its anti-CPV activity both in vitro and in vivo . Our results indicated that codon optimization could significantly improve sTfR expression in HEK293T cells. The prepared recombinant sTfR possessed a binding activity to both CPV and CPV VP2 capsid proteins and significantly inhibited CPV infection of cultured feline F81 cells and decreased the mortality of CPV-infected dogs, which indicates that the sTfR has the anti-CPV activity both in vitro and in vivo .